(untitled) - Orr, Bill (New York, 1992)
The 1990s were an extraordinary, contradictory, and fascinating period of economic development. Specifically, the 'boom' of the 1990s and the way that it ended evoked many historical precedents, particularly, past bubbles and 'busts'. In this book, contributions by eminent economic historians examine key issues such as the causes and sustainability of productive growth in the U.S., the sluggish growth in Europe and stagnation in Japan. They assess whether, seen in long-run perspective, the 1990s does actually fall into a familiar pattern of economic activity or whether it represents a watershed in economic history.
Keywords: Tài chính quốc tế,International finance